2023
DOI: 10.3390/biomedicines11051346
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Inorganic and Organic Selenium Compounds in Breast Cell Lines

Abstract: Triple-negative breast cancer (TNBC) is an aggressive, fast-growing tumor that is more likely to spread to distant organs. Among women diagnosed with breast cancer, the prevalence of TNBC is 20%, and treatment is currently limited to chemotherapy. Selenium (Se), an essential micronutrient, has been explored as an antiproliferative agent. Therefore, this study aimed to evaluate the effects of exposure to organic (selenomethionine, ebselen, and diphenyl diselenide) and inorganic (sodium selenate and sodium selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…In contrast, the effect of SeO 2 and selenium nanoparticles in this breast tumor cancer cell line provokes a diminish in cell viability but maintains at least 50% of cell viability [ 47 ]. Other inorganic selenocompounds have been evaluated in the literature in MDA-MB-231, all of them showing IC 50 values much higher than our synthesized compounds and with similar SIs [ 48 ]. On the other hand, the cytotoxicity of elemental Se has not been evaluated in the rest of the cancer cell lines studied herein, although the apoptotic cell death caused by elemental Se in DU-145 has been described [ 49 ].…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, the effect of SeO 2 and selenium nanoparticles in this breast tumor cancer cell line provokes a diminish in cell viability but maintains at least 50% of cell viability [ 47 ]. Other inorganic selenocompounds have been evaluated in the literature in MDA-MB-231, all of them showing IC 50 values much higher than our synthesized compounds and with similar SIs [ 48 ]. On the other hand, the cytotoxicity of elemental Se has not been evaluated in the rest of the cancer cell lines studied herein, although the apoptotic cell death caused by elemental Se in DU-145 has been described [ 49 ].…”
Section: Resultsmentioning
confidence: 81%
“…It should also be highlighted that Ebselen, a selenenylamide molecule, has been highly investigated throughout the years due to its GPx-mimicking activity and its antioxidant and electrophilic properties. Of note, a vast variety of clinical trials have been carried out to determine the therapeutic potential of this selenocompound in different pathological conditions such as Meinere’s disease, hypo/mania, and noise-induced hearing loss. Besides, a great number of studies have reported the potential application of this experimental drug against bacterial, viral, and fungal infections, , cancer cells, ischemia–reperfusion (I/R) injury, , tobramycin-induced ototoxicity, osteoarthritis, and Azheimer’s disease. Importantly, a growing body of compelling studies has shown that Ebselen can be a promising candidate for the treatment of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as it has proven to be an effective inhibitor of its main protease (M pro ), which is pivotal for the life cycle of this virus, by forming a selenosulfide bond with the thiol group of the catalytic cysteine (Cys) 145. Additionally, this experimental drug exhibited great anti-SARS-CoV-2 activity in infected Vero cells.…”
Section: Introductionmentioning
confidence: 99%
“…The strategic integration of selenium (Se) atoms into organic frameworks offers a promising avenue for the creation of enhanced, disease-specific compounds. Organoselenium compounds are renowned for their diverse pharmacological properties [9][10][11][12][13][14][15][16][17][18][19][20]. Furthermore, the biocompatibility, minimal toxicity, and chemical versatility of selenium have spurred the development of a diverse range of Se-based pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%